NEW FINANCIAL INSTRUMENTS OF LOCAL GOVERNMENT - B. R. Krasnickij (Модернизация, инновация, развитие, 2015)
This paper examines the current situation in the regulation authority for the formation of the revenue side of the budgets of municipalities, as well as an analysis of local government reform. The directions of development of the system of fi nancial support of local budgets, which will help to meet the diff erent needs of local communities.